Adaptive and energy-efficient solutions in modern bulldozer blade designs - Kerekelytsia, Nikita; Medvedskyi, Kostiantyn; Chopyk, Oleksandr (КНУБА, 2025)
The current trends in the development of bulldozer blades with an emphasis on their adaptability and energy efficiency are analyzed in the paper. The transition from traditional straight and spherical to transformed and specialized blades with expanders, two-blade and disk sections is considered. An overview of blade designs (PAT/VPAT, Σ-type, SU-blades) is presented with the comparative assessment of performance, capacity and energy consumption. The calculated assessment of the blade geometry influence on the volume of the soil drag prism and the technical performance of the bulldozer is performed. It is shown that the use of adaptive and energy-efficient blades allows to increase bulldozer performance by 20–40%, reduce specific fuel consumption by up to 15% and expand the versatility of use in various conditions.
Keywords: bulldozer; blade; design; energy efficiency; adaptability; performance; earthworks; soil